INDIGENOUS HERITAGE OF TRADITIONAL EMBROIDERY PRACTICED BY MEGHWAL COMMUNITY - Sharan, Madhu; Shah, Mitali; Agrawal, Dolly (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Artisanal skills in India are recognized as beautiful reflection in hand made arts and crafts. The present study was an attempt to document the history, origin, motifs, tools, and equipment’s used for embroidery practiced by Meghwal Community residing in Gujarat and Rajasthan. This type of embroidery is rare in its being; hence the main analysis of the study was to make people aware about Meghwal embroidery from the embroideries practiced by different communities. At present embroidery is mainly being practiced in two districts Bikaner (Rajasthan) and Kutch (Gujarat). A total sample comprised of 110 artisans of which 55 were from each district along with two NGO were selected one from each district. The sample selection criteria was determined by keep in view their involvement with Meghwal embroidery. According to the artisan, there was no significant difference in the embroidery practiced in Rajasthan and Kutch. The details of traditional style embroidery, as well as other information like existing motifs colour combinations, stitches, threads, and other raw materials was studied. According to the artisans and review of literature, Meghwal embroidery can be identified by its motifs and method of execution and motif development. The stitches are the same, but the identity of the embroidery practiced by the community is reflected in the methods of motif’s development, the fabric and colour combination was changed according to the market demand.